Ultra-High-Speed Image Signal Accumulation Sensor - Etoh, Takeharu Goji (Molecular Diversity Preservation International (MDPI), 2010)
Averaging of accumulated data is a standard technique applied to processing data with low signal-to-noise ratios (SNR), such as image signals captured in ultra-high-speed imaging. The authors propose an architecture layout of an ultra-high-speed image sensor capable of on-chip signal accumulation. The very high frame rate is enabled by employing an image sensor structure with a multi-folded CCD in each pixel, which serves as an in situ image signal storage. The signal accumulation function is achieved by direct connection of the first and the last storage elements of the in situ storage CCD. It has been thought that the multi-folding is achievable only by driving electrodes with complicated and impractical layouts. Simple configurations of the driving electrodes to overcome the difficulty are presented for two-phase and four-phase transfer CCD systems. The in situ storage image sensor with the signal accumulation function is named Image Signal Accumulation Sensor (ISAS).